Prevalence of Perkinsus spp. in selected shellfish species collected off China coast - Xie, L.; Xie, Z. (Indian Journal of Fisheries, 2019)
We investigated the prevalence of Perkinsus spp. in 13 species of shellfish collected from the coastal areas of China between 2006 and 2012. A total of 11,581 shellfish specimens belonging to 13 different species were collected from seven bay areas in China viz., Dalian (Bohai Sea), Qingdao (Yellow Sea), Wenzhou (East China Sea), Xiamen (East China Sea), Zhanjiang (South China Sea), Haikou (South China Sea) and Qinzhou (South China Sea). The shellfish samples collected were tested for the prevalence of Perkinsus spp. using a PCR protocol. The detection rates of Perkinsus spp. by PCR method ranged from 0.38 to 26.37%, with Ruditapes philippinarum (26.37%) and Paratapes undulatus (=Paphia undulata) (20.21%) showing the highest detection rate. The detection rate of Perkinsus spp. by PCR in oyster samples were highest in Wenzhou (17.25%), Qinzhou (15.98%) and Zhanjiang (11.67%) bays. Samples taken in autumn showed the highest positive detection rate. Mixed infection by Perkinsus spp. and other protozoan species viz., Haplosporidium nelsoni and Marteiliia spp. was found to be a common phenomenon (10.75%).